Civil society as a tool of civilized conflict resolution during the political and economic crisis in Ukraine - Довбня, О. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The role of civil society and its institutions in conflict resolution is explored. In particular, author puts an emphasis on the conflicts, which result in a deep political crisis. It is proved that without the activity of non-governmental organizations Ukraine will not be able to overcome its external dependence and sustain economic and cultural growth.